The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-07739-y
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the miRNA signature associated with survival time in patients with lung adenocarcinoma using miRNA expression profiles

Abstract: Lung adenocarcinoma is a multifactorial disease. MicroRNA (miRNA) expression profiles are extensively used for discovering potential theranostic biomarkers of lung cancer. This work proposes an optimized support vector regression (SVR) method called SVR-LUAD to simultaneously identify a set of miRNAs referred to the miRNA signature for estimating the survival time of lung adenocarcinoma patients using their miRNA expression profiles. SVR-LUAD uses an inheritable bi-objective combinatorial genetic algorithm to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 129 publications
0
40
0
Order By: Relevance
“…The feature selection algorithm IBCGA uses an intelligent evolutionary algorithm 82 to solve the large parameter optimization problem. IBCGA has been successfully applied in several bioinformatics problems, including the prediction of human ubiquitination sites 83 , the prediction of the regulatory roles of cyclic AMP receptor proteins 84 and the estimation of survival time for cancer patients 85 , 86 .…”
Section: Methodsmentioning
confidence: 99%
“…The feature selection algorithm IBCGA uses an intelligent evolutionary algorithm 82 to solve the large parameter optimization problem. IBCGA has been successfully applied in several bioinformatics problems, including the prediction of human ubiquitination sites 83 , the prediction of the regulatory roles of cyclic AMP receptor proteins 84 and the estimation of survival time for cancer patients 85 , 86 .…”
Section: Methodsmentioning
confidence: 99%
“…miR3934 is found upregulated in colon cancer and was suggested as a biomarker for lung cancer as its expression correlated with survival rate and prognosis of NSCLC [71,72]. Moreover, it has been reported that miR-3934-5p expression significantly increases in NSCLC cell line A549 [73]. It is also a SNP linked to TGF-β signalling and has been identified as downregulated in rectal carcinoma mucosa, compared with normal mucosa [74].…”
Section: Mir-3934-3pmentioning
confidence: 99%
“…Lung adenocarcinoma (LUAD) is the major type of NSCLC and the morbidity of LUAD has surpassed lung squamous carcinoma in recent years ( 5 ). Due to the deficiency of tumor diagnosis using the traditional bronchoscopy and computed tomography techniques, patients in the early stage of cancer are difficult to be detected ( 6 , 7 ). Therefore, it is imperative to find prognostic biomarkers that instruct the treatment of lung cancer.…”
Section: Introductionmentioning
confidence: 99%